Religious vs. Conventional Cognitive Behavioral Therapy for Major Depression in Persons With Chronic Medical Illness. Issue 4 (April 2015) - Koenig, Harold G.; Pearce, Michelle J.; Nelson, Bruce; Shaw, Sally F.; Robins, Clive J.; Daher, Noha S.; Cohen, Harvey Jay; Berk, Lee S.; Bellinger, Denise L.; Pargament, Kenneth I.; Rosmarin, David H.; Vasegh, Sasan; et al.
<x xml:space="preserve">Abstract</x> Abstract We examine the efficacy of conventional cognitive behavioral therapy (CCBT) versus religiously integrated CBT (RCBT) in persons with major depression and chronic medical illness. Participants were randomized to either CCBT (n = 67) or RCBT (n = 65). The intervention in both groups consisted of ten 50-minute sessions delivered remotely during 12 weeks (94% by telephone). Adherence to treatment was similar, except in more religious participants in whom adherence to RCBT was slightly greater (85.7% vs. 65.9%, p = 0.10). The intention-to-treat analysis at 12 weeks indicated no significant difference in outcome between the two groups (B = 0.33; SE, 1.80; p = 0.86). Response rates and remission rates were also similar. Overall religiosity interacted with treatment group (B = −0.10; SE, 0.05; p = 0.048), suggesting that RCBT was slightly more efficacious in the more religious participants. These preliminary findings suggest that CCBT and RCBT are equivalent treatments of major depression in persons with chronic medical illness. Efficacy, as well as adherence, may be affected by client religiosity.